Altered tryptophan catabolite concentrations in major depressive disorder and associated changes in hippocampal subfield volumes. (September 2018) - Doolin, Kelly; Allers, Kelly A.; Pleiner, Sina; Liesener, Andre; Farrell, Chloe; Tozzi, Leonardo; O'Hanlon, Erik; Roddy, Darren; Frodl, Thomas; Harkin, Andrew; O'Keane, Veronica
Highlights: Only fpMDD patients had decreased kynurenic acid compared to controls. rMDD patients had increased quinolinic acid compared to controls and fpMDD patients. Quinolinic acid was correlated to markers of inflammation in depressed patients. Depression scores were inversely correlated to kynurenic acid in depressed patients. Kynurenic acid and subiculum volume were positively correlated in MDD patients. Abstract: Background: Tryptophan depletion is a well-replicated biological finding in Major Depressive Disorder (MDD). The kynurenine pathway (KP) and its rate-limiting tryptophan degrading enzyme, indolamine 2, 3 dioxygenase (IDO), have been implicated in the pathogenesis of depression. IDO expression is driven by inflammatory cytokines, providing a putative link between inflammation and neuropathology. This study examined circulating concentrations of C-reactive protein (CRP), plasma tryptophan, kynurenine (KYN), kynurenic acid (KYNA) and quinolinic acid (QUIN) and whole blood mRNA expression of IDO in patients with major depressive disorder (MDD) compared with healthy controls (HC). Methods: A diagnosis of major depression was made according to DSM-IV. Depression severity was assessed using the Hamilton depression (HAM-D) rating scale. 74 MDD patients, 39 with a first presentation of MDD (fpMDD) and 35 with chronic or recurrent episodes (rMDD), and 37 HC were recruited to the study. Whole blood and plasma samples were collected. Expression of markers in whole blood were measured by PCR, circulating CRP by ELISA and KP metabolites by LC–MS/MS. Hippocampal cornu ammonis (CA) and subiculum volumes were determined by MRI and calculated using FreeSurfer. Results: Tryptophan concentrations were significantly reduced in MDD compared to HC. There was a positive correlation between QUIN and both CRP concentrations and whole blood IDO1 in MDD. KYNA concentrations were reduced in MDD patients presenting with a first episode (fpMDD) compared to those presenting with recurrent depression (rMDD) and HC. By contrast QUIN concentrations were elevated in rMDD compared to fpMDD and HC. KYNA/QUIN was reduced in MDD and rMDD but not fpMDD compared to HC. Hippocampal subfield volumes were smaller in MDD patients than HC for CA1 (left only), CA2/3 (left and right) and CA4 (right only). CRP and CA1 volumes were negatively correlated bilaterally in MDD patients. KYNA and subiculum volume were positively correlated bilaterally. Discussion: This study found evidence of KP metabolism imbalance in MDD patients in addition to tryptophan reduction and mild immune activation. Relationships between CRP and KYNA with some hippocampal subfield volumes in MDD patients suggest that this inflammatory signature may be associated with reduced hippocampal subfield volumes in depression.